2013
DOI: 10.1099/jmm.0.058354-0
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-resistance mechanisms of multidrug-resistant Pseudomonas aeruginosa

Abstract: Clonal dissemination of multidrug-resistant Pseudomonas aeruginosa (MDRPA) is a major concern worldwide. The aim of this study was to explore the mechanisms leading to the carbapenem resistance of an MDRPA clone. Isolates were obtained from a surgical wound, sputum, urine and a blood culture. Pulsed-field gel electrophoresis (PFGE) showed high genomic homogeneity of these isolates and confirmed the circulation of an endemic clone belonging to serotype O4. Outer membrane protein (OMP) bands were visualized by S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…Their results showed an overexpression of the MexAB-OprM efflux pump, and a functional MexXY-OprM was detected in all isolates (23).…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed an overexpression of the MexAB-OprM efflux pump, and a functional MexXY-OprM was detected in all isolates (23).…”
Section: Discussionmentioning
confidence: 99%
“…7, 8 The mechanisms of carbapenem resistance are strongly associated with carbapenemase production (acquisition of carbapenemase genes), combination of porin loss with extended-spectrum β-lactamases (ESBLs) and the overexpression of efflux pumps. 9,10 Several studies have reported that acquired carbapenemase isolates might cause hospital outbreaks and become endemic in healthcare settings. 11,12 Globally predominant carbapenemases include KPC, NDM, VIM, IMP, and OXA, which are encoded by bla KPC , bla NDM , bla VIM , bla IMP , and bla OXA genes present in both the plasmid and the chromosome.…”
Section: Introductionmentioning
confidence: 99%
“…Among the pathogens that affect the CF patients, Pseudomonas aeruginosa (PA) is the most prevalent, but the treatment of its infections is often difficult due to the wide range of antimicrobial resistance of this species. This resistance to antimicrobials is a well documented phenomenon due to several molecular mechanisms such as the restricted outer membrane permeability, the presence of integron, insertion sequences, and the biosynthesis of degrading-enzymes (Fuste et al, 2013;Ruiz-Martinez et al, 2011a;Ruiz-Martinez et al, 2011b). P. aeruginosa infections usually start as an acute infection that finally becomes chronic.…”
Section: Introductionmentioning
confidence: 99%